Numerical study on tunnel damage subject to blast-induced shock wave in jointed rock masses - Deng, X.F.; Zhu, J.B.; Chen, S.G.; Zhao, Z.Y.; Zhou, Y.X.; Zhao, J. (Tunnelling and underground space technology, 2014)
•Damage of rock tunnel subject to blast-induced shock wave is modeled with UDEC.•Effects of joint properties on tunnel damage are investigated.•Effects of initial stress and scaled distance on tunnel damage are determined.•Bolt supporting to tunnel stability is modeled.•Modeling results are compared with other available data. In this study, numerical modeling on the damage of existing circular tunnel subject to blast-induced shock wave was carried out with DEM-based code UDEC. The disturbed zones including failure zones, open zones and shear zones around circular tunnel and peak particle velocities (PPVs) at tunnel surface are employed to analyze the damage of tunnel. The effects of joint spatial and mechanical properties, initial stress of rock mass, and magnitude of shock wave amplitude to damage of tunnel were evaluated in this study. The difference of damage between non-supported circular tunnel and bolt-supported circular tunnel subject to the same blast-induced shock wave was also studied. It is found that the orientations of joints in rock mass around the tunnel have great effects on tunnel damage. The initial stress around tunnel has relatively small influence on tunnel damage. The bolt support could greatly increase the stability of tunnel by changing the vibration form of particle velocity rather than the decreasing of PPV.